The Development of Interactive Picture Card Media with QR Code to Improve IPAS Learning Outcomes - Wulansari, Desi; Tyas, Dewi Nilam (Jurnal Prima Edukasia, 2025)
One element that encourages increased student focus and makes it easier to understand the subject matter is learning media. This study aims to create and evaluate interactive picture card media with QR codes to enhance grade IV students' learning results. Research and Development (R&D), which is modified into nine phases until the final product revision, is the method used in this study. The research subjects are teachers, students, media specialists, and subject matter specialists. Data collection was conducted through observation, surveys, interviews, and documentation. The t-test, n-gain, and normality tests are the data analysis methods used in this investigation. The design validation results get very feasible criteria from media experts (92.28%) and material experts (92.18%). The results of the classroom teacher response were 93.75%, and the student response was 94.27%, which are feasible criteria. The significant effectiveness test using the t-test is 0.000, which indicates that Ha is accepted while Ho is rejected. The n-gain calculation is 0.6915 medium criteria. Thus, the interactive picture card media with the QR Code that has been developed is very feasible and effective for improving learning outcomes. These findings contribute to the development of innovative learning media that can enhance student learning outcomes and offer new alternatives for teachers in delivering lesson materials, especially at the elementary school level.